PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DALAM MENSTIMULASI KEMAMPUAN BERFIKIR KREATIF SISWA PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG DI MADRASAH IBTIDAIYAH - Siti Nurjanah; Pina Indah Sayekti; Wahyu Warastuti; Vitri Astuti; Yulia Maftuhah Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the application of Culturally Responsive Teaching (CRT) approach in stimulating the creative thinking ability of grade 1 madrasah ibtidaiyah students on the material of recognizing the shape of space. Using qualitative method with ethnographic approach, this research highlights the integration of local cultural values through contextual media in the form of traditional food, interactive technology such as wordwall, and problem-based learning model. Data were collected through observation, interviews, and documentation, with data analysis following the Miles and Huberman model. Data validity was based on triangulation of techniques and sources. The results showed that the Culturally Responsive Teaching (CRT) approach in stimulating the creative thinking ability of grade 1 madrasah ibtidaiyah students on the material of recognizing the shape of a space, including: (1) students can identify spatial shapes through objects such as onde-onde (ball), layer cake (block), and diamond cake (cube); (2) students are able to see spatial shapes from various perspectives, both through concrete and digital media, (3) students show creativity by associating spatial shapes with other objects around them; (4) students can develop ideas in detail and complete challenges on the wordwall. Overall, the CRT approach helps students understand the concept of building space in a relevant, meaningful way, and supports the development of creative thinking skills holistically.